PENINGKATAN KEMAMPUAN LITERASI DAN ADAPTASI TEKNOLOGI MELALUI PROGRAM KAMPUS MENGAJAR DI SEKOLAH DASAR No 5 SEJAJAH KABUPATEN BENGKAYANG - Warsidah Warsidah; Amriani Amir; Riza Linda; Mega Sari Juane Sofiana; Neva Satyahadewi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2022)
Teaching Campus is one of the main products of the Merdeka Learning Program Merdeka Campus which is a policy of the Minister of Education and Culture in an effort to encourage students to master various scientific fields in preparation for the world of work. The purpose of this campus teaching activity is to produce students with character, namely critical and creative as well as collaborative and skilled in every situation. The method used in this research is descriptive method, by describing all data obtained in research activities including primary, secondary and other supporting data to be analyzed and narrated in a structured, factual and systematic manner. Primary data was obtained through interviews with KM2 team students, students, teachers and principals as well as parents of SDN No 05 Sejajah students, while secondary data was based on literature review or based on references relevant to this research topic. The results of the research from the KM 2 activity which lasted for 20 weeks effectively showed that the role of the students participating in KM 2 had a positive impact on improving the quality of SDN No 05 Sejajah schools, especially in literacy and numeracy for students as well as technology adaptation and administrative order for school teachers. In addition, the motivation to go to school for the students of SDN No 05 Sejajah generally increased, indicated by the diligence and perseverance of the students attending and being in the classroom until the end of the lesson.Keywords: descriptive, technological adaptation, literacy, numeracy, SDN 05 Sejajah